Naratologi Musa Dalam Al-Qur’an Perspektif Stilistika - Hasbullah, M. (Dzil Majaz: Journal of Arabic Literature, 2024)
Each letter in the Koran has a harmonious sound that forms harmonious words, and several groups of words form a harmonious rhythm in a series of sentences, and in the end, these groups of sentences form a perfect rhythm in the verse. The beauty of the series of pronunciations and the accuracy of its meaning show that the Qur'an is a miracle that will never be equaled. This research aims to examine the language style and elements that make up the story about the Prophet Moses in the Koran and the impact it has. Stylistics is considered a suitable method for this purpose. The material object of this research is the story of the Prophet Musa in the Koran. The author uses library research, namely collecting data from various sources, analyzing it, and presenting the results of the data analysis. Some elements of language style found in this research are as follows: First, in terms of grammatical structure, there are four elements of language style, namely nouns, verbs, verbal sentences and nominal sentences. Second, in terms of lexical meaning, there are three elements of language style, namely antonyms, synonyms and polysemy. Third, in terms of fragments and cohesion, there is harmony in the plot of the story of the Prophet Moses in the Koran. Fourth, the effects are to attract sympathy, foster readiness, emphasize the message, and emphasize time